Myotonometry and extended field-of-view ultrasound imaging allow reliable quantification of patellar tendon stiffness and length at rest and during maximal load, whereas several restrictions exist for the Achilles tendon - Wegener, Florian; Ritterbusch, Arne; Saal, Christian; Baumgart, Christian; Hoppe, Matthias W. (Frontiers in Sports and Active Living, 2024)
Introduction Stiffness and length are well-established tendon parameters in sports and medicine. Myotonometry and ultrasound imaging are the commonly used methods to quantify these parameters. However, further studies are needed to clarify the reliability of these methods, especially when assessing maximally loaded tendons and when conducted by different experienced investigators. This study aimed to determine the intra- and interrater reliabilities of measuring the stiffness and length of the patellar tendon (PT) and Achilles tendon (AT) using the myotonometry method and the extended field-of-view ultrasound (EFOV-US) technique at rest and maximal load performed by different experienced investigators. Methods Twenty-seven participants were examined on three different days by one experienced investigator and one novice investigator. Primary outcomes were the intraclass correlation coefficient (ICC) and associated 95% confidence interval (95% CI), coefficient of variation (CV), standard error of measurement (SEM), and minimal detectable change (MDC) across the measurement days and investigators. Results For PT measurements at rest and maximal load, the estimated ICCs for stiffness and length were ≥.867 and ≥.970, respectively, with 95% CIs ranging from poor (.306) to excellent (.973) and good (.897) to excellent (.999). The CV, SEM, and MDC for PT stiffness and length were ≤5.2% and ≤2.0%, ≤39.3 N/m and ≤0.9 mm, and ≤108.9 N/m and ≤2.6 mm, respectively. For AT measurements, some restrictions were evident for stiffness at rest and both parameters at maximal load. However, regarding AT length at rest, the estimated ICC was ≥.996, with an excellent 95% CI (.987–.999). The CV, SEM, and MDC for AT length at rest were 2.8%, ≤1.1 mm, and ≤2.9 mm, respectively. Conclusion The estimated ICCs show good to excellent reliability for the myotonometry method and the EFOV-US technique for measuring PT stiffness and length at rest and maximal load for experienced and novice investigators. However, some restrictions are evident for the AT, especially for measurements at maximal load.